Roca Cabau, G. (2020). Pobresa i hospitals a la Lleida baixmedieval. Lleida: Pagès editors. 260 pp. ISBN: 978-84-1303-228-3 - Frederic Aparisi Romero (Universidad de Alicante, 2021)
Resenya: Roca Cabau, G. (2020). Pobresa i hospitals a la Lleida baixmedieval. Lleida: Pagès editors. 260 pp. ISBN: 978-84-1303-228-3.